A trust-based secure AODV routing scheme for MANET. (17th December 2021) - Wahi, Charu; Chakraverty, Shampa; Bhattacherjee, Vandana
Secure routing in mobile ad hoc networks remains to be a challenging research problem due to the dynamic and distributed nature of the operation. Cryptographic approaches to establish secured routing are not quite suitable for ad hoc networks because of the inevitable presence of a third party and due to high computational overheads involved. A viable alternative approach stems from the trust-based communication protocol embedded in the network layer. We introduce a trust-based solution named trust-based secure AODV (TSAODV), to establish a secure and reliable inter-node communication with minimal memory and communication overhead. Each node's trustworthiness is assessed based on its current performance as well as its past behaviour. Simulation results demonstrate that the proposed trust driven model improves packet delivery ratio and throughput as compared with conventional ad hoc routing schemes while minimising the penalty in terms of end-to-end delay.